RNA Nanotechnology and Therapeutics: Methods and Protocols - Guo, Peixuan (Springer, 2015)
This volume contains a compilation of techniques and laboratory protocols directly related to RNA nano technology and its applications in nano biotechnology and nano medicine. The chapters in this book cover a wide range of research methods that can be easily comprehended and carried out in a step-by-step manner by graduate students and postdoctoral fellows from diverse scientific disciplines. Some of the covered topics include various biochemical, biophysical and bioinformatics approaches for analyzing RNA structures and properties; methods to analyze the multi-step assembly process of RNA nano architectures; purification of multifunctional RNA nanoparticles by ultracentrifugation and HPLC; real-time detection of RNA nano constructs in vivo; conjugation of imaging, targeting and therapeutic modules to RNA scaffold; and design and characterization of RNA-protein nanostructures. Written in the highly successful Methods of Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols and key tips on troubles troubleshooting and avoiding known pitfalls.